PERSEPSI PASIEN TERHADAP PERILAKU CARING PERAWAT DI RUANG RAWAT INAP - Safdara Tika; Bayhakki Bayhakki; Widia Lestari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Improving the quality of nursing services can be improved through the provision of nursing care based on caring. The caring behavior of nurses in the world today has begun to improve, but there are still some countries where the caring behavior of nurses is bad. The purpose of this study was to determine the patient's perception of the caring behavior of nurses in the inpatient room at Awal Bors Panam Hospital. The method used in this research is descriptive quantitative. This research was conducted in July 2022. The sample in this study was 84 people who were selected by accidental sampling technique. The results of this study indicate that the majority of respondents are in the late elderly (56-65 years) as many as 24 (28.6%), have high school education as many as 27 (32.1%) and the length of stay for 4 days is 15 (17.9%), have a good perception of the caring behavior of nurses as many as 79 (94%), based on the respectful deference to the other sub scale, 53 (63.1%), based on assurance of human precense, 64 (76.2%), positive connectedness, 73 (86.9) good perceptions. %), based on professional knowledge and skills have very good perception as many as 54 (64.3%), and based on attentiveness to the other's experience have very good perception as many as 71 people (84.5%).Conclusion: that the patient's perception of the caring behavior of nurses is good, meaning that nurses have caring behavior towards all hospitalized patients..Keyword : Nurse Caring Behavior, Patient Perception